Burns and Shakespeare - Kuosaitė, Elena (Literatūra, 1973)
Many critics of the nineteenth and the twentieth centuries had pointed out the link between Burns and Shakespeare. But still the question has not received a more extensive elucidation.Burns' and Shakespeare's approaches towards the phenomena they deal with in their writings are different. Burns was a lyrical poet in the first place and his creation reflects the poet's subjective attitude to the world, his personal feelings. Shakespeare was a dramatist and a very objective writer, observation and statement dominates in his creation. Even in his lyrical poetry there is less of self-expression than in Burns' songs.But on the other hand, there are many common features in Burns' and Shakespeare's artistic method. The tragi-comic vision of the world, the blend of the ridiculous and the terrible, the realistic and the romantic are important elements of their creation. In this respect the most "shakespearian" of Burns' works are his poems "Tam o'Shanter" and "The Jolly Beggars".Both writers are similar to each other because of their concept of man and their view on moral values. Burns as well as Shakespeare looks for real values not in man's external features (his appearance, social position etc.) but in his moral qualities. This idea is often linked with the image of clothes in the works of both writers.One finds a link between Burns and Shakespeare also in their interest and employment of folk song tradition. There is, of course, a wider response to folk tradition in Burns' poetry, but songs and ballads or their snatches are various in their functions and poetical forms in Shakespeare's plays, too.
Keywords: -